Source Identification of brGDGTs in the Surface Sediments of the East China Sea - Wang, Yipeng; Yang, Jialei; Wang, Guichen; Zhang, Yinyi; Zhang, Rui; Li, Tiegang; Russell, James; Wang, Jiayue; Wang, Xinling; Zhang, Fan; Song, Yuehua; Yu, Xiaoxiao; et al. (Frontiers in Earth Science, 2022)
Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are components of bacterial membranes in terrestrial soils, which are widely used in paleoenvironmental reconstruction in global terrestrial soils and marine sediments. In marine sediments, the mixed sources of brGDGTs complicate the applications of brGDGT-related indicators in reconstructing terrestrial environments. In this study, we reported the spatial distribution of brGDGT-related indicators (MBTʹ 5ME, CBTʹ 5ME, #Ringstetra, and IIIa/IIa) in surface sediments from the East China Sea (ECS). MBTʹ 5ME and CBTʹ 5ME showed a stepped trend from the inner shelf to the outer shelf, and #Ringstetra and ∑IIIa/∑IIa values in sediments of the ECS are distinct compared with those in the catchment soils, suggesting marine in situ production of brGDGTs. We also examined the existence of marine in situ brGDGTs and quantitatively determined the contributions of terrestrial and in situ production of brGDGTs. This study reported mixed sources of soil-derived brGDGTs were dominant, and marine in situ brGDGTs were overprinted. Our results indicate that there were predominantly marine in situ brGDGTs (avg. 60.5 ± 5.5%) in the outer shelf due to the weak riverine transportation and were characterized by high #Ringstetra and IIIa/IIa.